Answer:
n = 7/2
Explanation:
We are given the equation:-
![\displaystyle \large{8 * √(2) = {2}^(n) }](https://img.qammunity.org/2022/formulas/mathematics/high-school/vdbsqz2eqszr90kfu9fnnf8a3uc39165zu.png)
To solve an exponential equation, first, we convert the whole equation with same base.
Let our main base is 2 for whole equation, the following number must be:-
- 8 = 2•2•2 = 2^3
- √2 = 2^(1/2) —> Law of Exponent
From √2 = 2^(1/2) comes from:-
![\displaystyle \large{ {a}^{ (m)/( n ) } = \sqrt[n]{ {a}^(m) } }](https://img.qammunity.org/2022/formulas/mathematics/high-school/z2mweo5ebtii10ge1ejgfhagehkmekcs2z.png)
![\displaystyle \large{ {2}^{ (1)/( 2 ) } = √(2) }](https://img.qammunity.org/2022/formulas/mathematics/high-school/85u9ae80sfgxe2aqad63rjq54jb9ms2ame.png)
Rewrite the equation with base 2.
![\displaystyle \large{ {2}^(3) * {2}^{ (1)/(2) } = {2}^(n) }](https://img.qammunity.org/2022/formulas/mathematics/high-school/vm3fhmko0e4pmw8px4vdnw8110itncpjlz.png)
Recall the law of exponent:-
![\displaystyle \large{ {a}^(m) * {a}^(n) = {a}^(m + n) }](https://img.qammunity.org/2022/formulas/mathematics/high-school/vwenmlvk28bxa7y8l5xzmwvut8fc8jvxs9.png)
Therefore:-
![\displaystyle \large{ {2}^{3 + (1)/(2) } = {2}^(n) } \\ \displaystyle \large{ {2}^{ (6)/(2) + (1)/(2) } = {2}^(n) } \\ \displaystyle \large{ {2}^{ (7)/(2) } = {2}^(n) }](https://img.qammunity.org/2022/formulas/mathematics/high-school/qe362dtwomhk0jfvrrcsg6enu7nl0laon8.png)
Compare the exponent and thus:-
n = 7/2.